Improvement of wear-resistant properties of steel 30Н3MF with additional microalloying - A. Z. Issagulov; Sv. S. Kvon; V. Yu. Kulikov; A. M. Dostaeva; E. P. Shcherbakova; P. V. Kovalev (Литьë и металлургия)
One of the directions of wear resistance improvement is microalloying of improved steels. In the studies conducted, the feasibility of adjusting the composition of steel 30Н3MF was determined by additional microalloying of V + Nb in order to give it wear-resistant properties. Microstructural studies of the experimental alloy were carried out. The microstructure is fairly uniform, represented by a matrix and inclusions. Matrix is represented by doped solution, which includes nickel. It is determined that in a chemically and structurally inhomogeneous ingot, even after heat treatment, structural components will remain. Characteristics such as the amount, morphology and distribution of non-metallic inclusions in the metal matrix are mainly laid at the stage of metal discharge from the steelmaking unit, as well as in the process of deoxidation and modification of steel during its off-furnace treatment.